The Effectiveness of Book Creator in Improving the Indonesian Language Learning Outcomes of Seventh-Grade Students at SMP Negeri 1 Baranti, Sidenreng Rappang Regency - Nurul Safika; Syamsunir; Muhammad Takdir; Madaling (Edumaspul: Jurnal Pendidikan, 2026)
This study examined the effectiveness of Book Creator in improving Indonesian language learning outcomes among seventh-grade students at SMP Negeri 1 Baranti, Sidenreng Rappang Regency. A quantitative approach was employed using a one-group pretest-posttest design. All 39 students from classes VII.1 and VII.2 participated through total sampling. Data were collected using a 25-item multiple-choice achievement test, classroom observation, and a dichotomous questionnaire covering learning-goal mastery, learning outcomes, student activity and discipline, and overall behavioral change. The main data were analyzed using descriptive statistics and a paired-samples t-test. The mean pretest score of 54.05 (SD = 20.50) increased to 88.10 (SD = 8.33) on the posttest, representing a mean gain of 34.05 points. The number of students attaining the minimum score of 70 rose from 11 students (28.2%) to 38 students (97.4%). The paired-samples test showed a statistically significant difference, t(38) = 10.748, p < .001. Students also gave positive responses across the supporting indicators. These findings indicate that Book Creator was effective in improving Indonesian language learning outcomes in the investigated classroom context while supporting active and positive learning behavior